Gallbladder lymphoma detected by 18F-fluorodeoxyglucose positron emission tomography - Alvin So (World Journal of Nuclear Medicine, 2020)
Gallbladder involvement in lymphoma is rare, with only a few cases reported in the literature, predominately in the pre positron emission tomography (PET) era. 18F-fluorodeoxyglucose (18F-FDG) PET/computed tomography (CT) has now become the modality of choice in the staging of lymphoma. We report a case of gallbladder involvement by high-grade B-cell lymphoma detected by PET/CT.